2021
DOI: 10.1002/pds.5245
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of how missing data are handled and reported in multi‐database pharmacoepidemiologic studies

Abstract: Purpose: Pharmacoepidemiologic multi-database studies (MDBS) provide opportunities to better evaluate the safety and effectiveness of medicines. However, the issue of missing data is often exacerbated in MDBS, potentially resulting in bias and precision loss. We sought to measure how missing data are being recorded and addressed in pharmacoepidemiologic MDBS.Methods: We conducted a systematic literature search in PubMed for pharmacoepidemiologic MDBS published between 1st January 2018 and 31st December 2019. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We observed this most often in the assessment of bias due to missing data. This poor reporting is not specific to COVID‐19 research and has also been observed for pharmacoepidemiologic studies in general 30,31 . Understandably, due to word limits, authors are unable to elaborate on all methodological decisions in their manuscript.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed this most often in the assessment of bias due to missing data. This poor reporting is not specific to COVID‐19 research and has also been observed for pharmacoepidemiologic studies in general 30,31 . Understandably, due to word limits, authors are unable to elaborate on all methodological decisions in their manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…This poor reporting is not specific to COVID-19 research and has also been observed for pharmacoepidemiologic studies in general. 30,31 Understandably, due to word limits, authors are unable to elaborate on all methodological decisions in their manuscript. However, in situations where methods deviate from generally accepted methods, substantiation of choices that were made is needed for correct interpretation of the results of a study as well as for assessment of its validity.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…For the use of real‐world evidence (RWE) in the regulatory realm, both the US Food and Drug Administration and the European Medicines Agency have pointed out the challenges posed by missing data, recommending a series of approaches based on methods such as inverse probability weighting or likelihood‐based methods 21 as well as multiple imputation approaches, 22 given full transparency regarding the assumptions required for validity of these methods, 23‐28 and accompanied by sensitivity analyses 25 . Recent literature has noted that few studies address how missingness assumptions are actually checked, or how the missingness is handled in analyses; studies that propose recommendations do so in a non‐systematic fashion 12,19,29,30,31,32,33 . Our workflow is an easy‐to‐implement approach to check analytical assumptions around the potential mechanisms of missingness of critical variables before conducting further downstream analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although complete case analysis is often used in medical studies [25] it has its limits, especially when the reason for dropouts is not known [26]. For the necessary randomized trial measures to prevent dropouts like reminders and recruitment via medical personnel should be implemented as well as investigations concerning the dropout reason.…”
Section: Discussionmentioning
confidence: 99%